Coherent J/psi photoproduction in ultra-peripheral PbPb collisions at root s(NN)=2.76 TeV with the CMS experiment - (:unkn) unknown (ELSEVIER, 2017)
The cross section for coherent J/psi photoproduction accompanied by at least one neutron on one side of the interaction point and no neutron activity on the other side, Xn0n, is measured with the CMS experiment in ultra-peripheral PbPb collisions at root sNN= 2.76TeV. The analysis is based on a data sample corresponding to an integrated luminosity of 159 mu b(-1), collected during the 2011 PbPb run. The J/psi mesons are reconstructed in the dimuon decay channel, while neutrons are detected using zero degree calorimeters. The measured cross section is d sigma(Xn)o(n)(coh)/dy(J/psi) = 0.36 +/- 0.04 (stat)+/- 0.04 (syst) mbin the rapidity interval 1.8 <vertical bar y vertical bar < 2.3. Using a model for the relative rate of coherent photoproduction processes, this Xn0nmeasurement gives a total coherent photoproduction cross section of d sigma(coh/) dy(J/psi) = 1.82 +/- 0.22 (stat)+/- 0.20 (syst)+/- 0.19 (theo) mb. The data strongly disfavorthe impulse approximation model prediction, indicating that nuclear effects are needed to describe coherent J/psi photoproduction in.+ Pbinteractions. The data are found to be consistent with the leading twist approximation, which includes nuclear gluon shadowing. (C) 2017 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Heavy ion collisions; Ultra-peripheral collisions; UPC; J/Psi; DISSOCIATION; PHYSICS; MESONS